2008
DOI: 10.1007/s11294-008-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

Taylor Rule in Practice: Evidence from Turkey

Abstract: Turkey, Inflation targeting, Taylor rule, Monetary policy, Reaction function, GMM, E40,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The empirical Taylor rule estimated in this paper is a forward-looking one of the following form:where it is the interest rate set by the central bank, and r¯ is the equilibrium real interest rate, which is unobserved and is measured by the constant in the regression as in most studies (e.g. Razzak, 2003; Adanur Aklan and Nargelecekenler, 2008; Belke and Klose, 2009; Judd and Rudebusch, 2020). πt+k and yt+k are the k-period ahead forecasts of inflation and the output gap respectively, and ut is an error term.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…The empirical Taylor rule estimated in this paper is a forward-looking one of the following form:where it is the interest rate set by the central bank, and r¯ is the equilibrium real interest rate, which is unobserved and is measured by the constant in the regression as in most studies (e.g. Razzak, 2003; Adanur Aklan and Nargelecekenler, 2008; Belke and Klose, 2009; Judd and Rudebusch, 2020). πt+k and yt+k are the k-period ahead forecasts of inflation and the output gap respectively, and ut is an error term.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…The first group of studies estimates a linear reaction function for the CBRT. For instance, while Berument and Malatyali (2000) found that the CBRT considers past inflation rates rather than expected inflation rates, Adanur-Aklan and Nargelecekenler (2008) concluded that it is concerned with both past inflation and expected inflation rates. Berument and Tasci (2004) found that the central bank deals with only the output gap while Yazgan and Yilmazkuday (2007) concluded that it responds to changes in both expected inflation rates and the output gap.…”
Section: Brief Overview Of the Literature And Contributions Of This Amentioning
confidence: 99%
“…First, there are many papers estimating the reaction function of the CBRT in the empirical literature (see e.g., Berument and Malatyali, 2000;Berument and Tasci, 2004;Yazgan and Yilmazkuday, 2007;Adanur-Aklan and Nargelecekenler, 2008;Erdem and Kayhan, 2010;Gozgor, 2012;Bulut, 2016). Among these papers, some add financial variables to the reaction function of the CBRT (Berument and Malatyali 2000;Berument and Tasci, 2004;Yazgan and Yilmazkuday, 2007;Erdem and Kayhan, 2010;Gozgor, 2012).…”
Section: Introductionmentioning
confidence: 99%